Pengaruh Visual Packaging, UGC, dan Social Proof terhadap Purchase Intention Produk Kecantikan Lokal di Kalangan Generasi Z Indonesia - Cinta Dwi Alieka; Ida Farida Oesman; Dadan Abdul Aziz Mubarok; Ridho Riadi Akbar; Rama Chandra Jaya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research was conducted with the aim of examining the impact of visual packaging, user-generated content (UGC), and social proof in stimulating purchase intention of local beauty products among Indonesian Generation Z respondents. By adopting the Stimulus-Organism-Response (SOR) theory, this study focused on the non-market leader local cosmetic product category to obtain an objective picture of consumer behavior. Through a quantitative approach, data were collected from 150 respondents through purposive sampling with a Likert scale questionnaire of 1 to 5, then processed through multiple linear regression techniques with the help of IBM SPSS 31 software. The research findings confirmed that visual packaging, UGC, and social proof simultaneously had a significant effect on purchase intention (Adjusted R² = 0.641). The results of the partial test showed that social proof was the most dominant factor (β = 0.356; p < 0.001) compared to UGC (β = 0.277; p = 0.008) and visual packaging (β = 0.236; p = 0.005). From a theoretical perspective, these findings strengthen the relevance of the SOR model in explaining how social validation is a key driver for Generation Z in determining purchase intentions. Practical implications: Local beauty product businesses are advised to combine visual elements with social proof strategies to strengthen consumer purchase intentions.